Out-of-field dosimetry and 2nd cancer risk assessment of child patients under proton therapy using a TLD-based microdosimeter. (November 2017) - Mukherjee, Bhaskar; Fuentes, Carolina; Lambert, Jamil
Abstract: A passive microdosimeter based on TLD-700 ( 7 LiF: Mg, Ti) and BeO chips was used to assess the dose equivalent (H), average LET (Lav ) and quality factor (Q) of secondary radiations at out-of-field organs of child patients undergoing proton therapy. Six sets of microdosimeters were cross calibrated using a gas-filled tissue equivalent proportional counter (TEPC) exposed to stray radiation field produced by bombarding a polystyrene plate phantom (30 cm × 30  cm × 40 cm) with therapeutic proton beam of energies 81, 119, 150, 177, 201 and 231 MeV. The resulting H, Lav and Q were presented as linear functions of TL glow curve area ratio (ABeO /ATLD700 ) of the dosimeters pairs evaluated using a common TLD reader. Subsequently, the calibrated microdosimeters were attached to the locations of thyroid, left and right brest/lung and stomach of two child cancer patients of interest. After the completion of therapeutic proton exposure the TLD chips were removed from the child's body, read out and the values of H, Lav and Q at relevant organ locations evaluated. Using the organ, gender and age specific risk coefficients (R T ) the lifetime attributable risks of the 2nd cancer (LAR T ) were calculated. Highlights: A polystyrene phantom bombarded with energetic proton beams from a cyclotron. TLD-700/BeO pairs and a TEPC exposed to secondary radiation field. H, Lav and Q were evaluated as functions of TLGC area ratio. Calibrated TLD chips were placed on o-o-f organ locations of child patients. LAR of the 2nd cancer was calculated using TLD results and risk factors.